Chromatin Remodeling Complexes: The Regulators of Genome Function - Shashibhal M Pandey (Global Journal of Zoology - Peertechz Publications, 2016)
Genome in eukaryotes is large enough to be accommodated in tiny nucleus. It is required to achieve high degree of compaction for getting into the nucleus. Compaction is achieved by folding the DNA in the form of chromatin. But chromatin acts as general repressor for the entire genomic functions. Therefore, it requires being selectively unpacked for gene expression. However this packing and unpacking of chromatin need to temporally and spatially regulated for differential regulation of genomic functions like DNA replication, repair, recombination and transcription. Chromatin remodeling factors regulate structure and function of chromatin in time and space to facilitate various genomic functions. Chromatin remodeling complexes can be broadly categorized into those that carry out remodeling by utilizing energy from ATP hydrolysis and those that covalently modify chromatin proteins and thus bring about permanent yet reversible alteration in the chromatin structure.